Natural history of celiac disease-associated antibodies and progression to overt disease in children at increased genetic risk - Simell, Satu (Annales Universitatis Turkuensis D 936, 2010)
Background: Celiac disease is a lifelong, gluten-sensitive, autoimmune-mediated chronic enteropathy, tightly associated with risk alleles at the HLA class II genes. Aims: This study was carried out as a part of the population-based Type 1 Diabetes Prediction and Prevention (DIPP) Project. The first aim was to study the natural history of celiac disease-associated antibodies before the diagnosis of celiac disease was made. The second aim was to describe when and in which order celiac disease-associated and type 1 diabetes-associated antibodies appeared in children with genetic risk for both diseases. Subjects and Methods: Antibodies against tissue transglutaminase (TGA) and other celiac disease-associated antibodies were measured in serum samples collected at 3- to 12-month intervals of children at genetic risk for celiac disease who participated in the DIPP project. Celiac disease was confirmed by duodenal biopsy. Type 1 diabetes-associated antibodies were measured in all samples that had been collected. Overt disease was diagnosed according to World Health Organization criteria. Follow-up continued until a diagnosis of type 1 diabetes or until the end of a defined follow-up period. Results: TGA appeared in children at genetic risk for celiac disease only after the first year of life, but anti-gliadin antibodies often emerged significantly earlier, at age 6 months. The data show that spontaneous disappearance of celiac disease-associated antibodies, transient or persisting, is a common phenomenon, at least in prepubertal children. In children with genetic susceptibility to type 1 diabetes and celiac disease, celiac disease-associated antibodies usually develop earlier than the type 1 diabetes-associated antibodies. Conclusions: The transient nature of celiac disease-associated antibodies emphasizes the significance of establishing seropositivity repeatedly in screening detected celiac disease before gastroscopy and duodenal biopsy are considered and emphasized the importance of duodenal biopsy for diagnosing celiac disease.